Characteristics and outcomes of pediatric oncology patients at risk for guardians declining transfusion of blood components. Issue 1 (6th July 2022) - Stevenson, Jason; DeGroote, Nicholas P.; Keller, Frank; Brock, Katharine E.; Bergsagel, D. John; Miller, Tamara P.; Cornwell, Patricia; Fasano, Ross; Chonat, Satheesh; Castellino, Sharon M.
Abstract: Background: Transfusion of blood products is a necessary part of successful delivery of myelosuppressive regimens in pediatric cancer. There is a paucity of literature characterizing outcomes or management of pediatric patients with cancer when transfusion is declined. Aims: The objective of this paper is to describe the clinical characteristics, care, and outcomes of patients with cancer at risk for declining transfusion. Methods and Results: A retrospective cohort of patients aged 0–21 years with cancer managed at Children's Healthcare of Atlanta between 2006 and 2020 and with ICD‐9 codes indicating risk of "transfusion refusal" or Jehovah's witness (JW) religion was identified. Demographics, disease, and management were abstracted. Descriptive statistics were performed to examine associations with transfusion receipt. Among 35 eligible patients identified as at risk for declining transfusion, 89% had primary guardians who identified as JW, and 45.7% identified as Black, non‐Hispanic. Only 40% of guardians actively declined transfusion. Transfusion recipients had significantly lower hemoglobin (g/dl) and platelet counts (1000/μl) at initial presentation (9.6 vs. 11.9, p  < .002 and 116.0 vs. 406.5, p  = .001, respectively) and at nadir (5.9 vs. 8.7, p  < .001 and ≤ 10 vs. 154, p  < .001, respectively) than non‐recipients. Legal intervention was required in 36.4% of those who ultimately received a transfusion. Conclusion: Among pediatric cancer patients whose medical record initially indicated a preference for no transfusion, 60% of guardians accepted blood products when prescribed for oncology care. Guidelines for systematic management and transfusion sparing approaches are needed to honor guardian's preferences when possible yet while maintaining equitable cancer outcomes in this population.